(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In the study "Risultati di un triennio di catture di afidi con trappola a suzione e segnalazione di tre specie nuove per l’Italia" (Limonta & Colombo, 1991) the species Pleotrichophorus persimilis Börner was wrongly recorded. The three individuals, catched by a Taylor suction trap at Ponte in Valtellina (Sondrio), actually belong to the congeneric species P. glandulosus (Kaltenbach) already recorded for Italy. The two aphids colonise two different species of Artemisia: P. persimilis develops on A. campestris, while P. glandulosus settles on A. vulgaris. Morfologically they differ for the lenght of siphunculi, longer in P. persimilis which presents hairs on the apical segment of rostrum of the same lenght while P. glandulosus has basal hairs 2-3 times as long as the distal ones (Hille Ris Lambers, 1953). Alate vivipare females present 2-8 and 14-23 secondary rhinaria rispectively on the third antenna! segment.